Acceptability of HIV self-testing: a systematic literature review - Janne Krause; Friederike Subklew-Sehume; Chris Kenyon; Robert Colebunders (2013)
The uptake of HIV testing and counselling services remains low in risk groups around the world. Fear of stigmatisation, discrimination and breach of confidentiality results in low service usage among risk groups. HIV self-testing (HST) is a confidential HIV testing option that enables people to find out their status in the privacy of their homes. We evaluated the acceptability of HST and the benefits and challenges linked to the introduction of HST.A literature review was conducted on the acceptability of HST in projects in which HST was offered to study participants. Besides acceptability rates of HST, accuracy rates of self-testing, referral rates of HIV-positive individuals into medical care, disclosure rates and rates of first-time testers were assessed. In addition, the utilisation rate of a telephone hotline for counselling issues and clients` attitudes towards HST were extracted.Eleven studies met the inclusion criteria (HST had been offered effectively to study participants and had been administered by participants themselves) and demonstrated universally high acceptability of HST among study populations. Studies included populations from resource poor settings (Kenya and Malawi) and from high-income countries (USA, Spain and Singapore). The majority of study participants were able to perform HST accurately with no or little support from trained staff. Participants appreciated the confidentiality and privacy but felt that the provision of adequate counselling services was inadequate.The review demonstrates that HST is an acceptable testing alternative for risk groups and can be performed accurately by the majority of self-testers. Clients especially value the privacy and confidentiality of HST. Linkage to counselling as well as to treatment and care services remain major challenges.